Start to draw : visual communication in the workplace - Vanquaillie, Axelle, ....- (Tielt : Lannoo, 2019)
Drawing enhances memorisation, understanding, talking and listening and sparks communication. It is a universal language, and can help you convey your message more clearly and engagingly - especially during meetings, while laying out ideas or simply in a brainstorming session. So why have all of us stopped drawing at a certain point in our lives? Start to Draw is a fun and clear-cut guide to drawing and visualising your ideas in your work environment. It is an accessible, bite-size book providing insight into why drawing works, how you can have a great impact on your own (and others') professional work, and how you can end up with a more creative approach to your job.
Visueel communiceren ; Management ; Interne communicatie